Soil Landscape Relationship of the Dune Infected Precambrian Pedeplane Area in South-Western Part of Haryana - Khanna, S S; Ahuja, R L; Manchanda, M L; Sangwan, B S; Goyal, V P (Annals of Arid Zone, 2016)
Soil Survey of dune infected precambrian pedeplane in south west Haryana was carried out covering an area of 33,000 hectares. Based on this survey landscape-soil relationship has been established. Four geomorphic units were identified in the area, i.e. Dunes (unstabilised)-severe1y eroded, non-calcareous, Typic Torripsamments; Dunes (stabilised)-moderately eroded, non-calcareous, Typic Torripsamments; Plain-coarse loamy, non-calcareous, Arenic Camborthids; and Depression with coarse loamy, calcareous, Typic Paleorthids. 55% of the area was covered by sand dunes stabilised; 25% by shifting sand dunes, 11% by depression and 9% by the plain.